Power Quality Enhancement in a Wind Farm Connected Grid with a Fuzzy-based STATCOM - Adware, Ramchandra; Chandrakar, Vinod (Engineering, Technology & Applied Science Research, 2023)
Integrating wind farms with electricity transmission networks presents several problems, and power quality plays a vital role among these. This study proposed a novel fuzzy logic controller to reduce the effect of power quality issues in such applications and investigated two different FACTS (Flexible AC Transmission System) devices, the Static Var Compensator (SVC) and the Static Synchronous Compensator (STATCOM). The fuzzy logic controller was designed as a voltage controller to improve power quality. Detailed analysis was carried out to investigate the successful mitigation of voltage sag/swell, active and reactive power improvement, and voltage flickers control by two controllers in a Multi-Terminal Load (MTL) system consisting of wind generators. The results were verified in MATLAB simulations, and a comparison was performed between the proposed shunt controllers. Furthermore, the design of a fuzzy interference system based on Vref (reference voltage) and the voltage measured at STATCOM location signals was investigated and compared with the SVC in terms of voltage sag, voltage swell, voltage flickers, and Total Harmonic Distortions (THD). The proposed fuzzy system was compared with a PI-based STATCOM and SVC. The power quality issues were exacerbated when using Multi-Terminal Load (MTL) in the transmission network.